2006
DOI: 10.1080/02841850600854902
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic difficulties in the management of H-type tracheoesophageal fistula

Abstract: Although symptoms are usually present from birth, the diagnosis of H-type fistula is difficult and often delayed. The various diagnostic techniques are not entirely reliable and fistula identification can be elusive. The authors present recommendations for the diagnostic work-up, which may increase the diagnostic potential and avoid unnecessary delays in the diagnosis and management of H fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 18 publications
(21 reference statements)
1
53
0
12
Order By: Relevance
“…Direct sagittal CT, three-dimensional CT and virtual bronchoscopy were all reported to be sensitive to detect H-type TEF [15,16]. HRCT warned us about the H-type TEF and we decided to perform bronchoscopy at first despite the radiological diagnosis of achalasia.…”
Section: Discussionmentioning
confidence: 97%
“…Direct sagittal CT, three-dimensional CT and virtual bronchoscopy were all reported to be sensitive to detect H-type TEF [15,16]. HRCT warned us about the H-type TEF and we decided to perform bronchoscopy at first despite the radiological diagnosis of achalasia.…”
Section: Discussionmentioning
confidence: 97%
“…This would increase the diagnostic potential and avoid unnecessary delays in the management. 3,7,8 However, in the critically ill premature infant, invasive investigations could not be performed as being potentially hazardous, and not always easy to achieve. Ou et al 10 reported that the high-resolution CT scan with air distention of esophagus to be a valuable diagnostic utility as an alternative noninvasive modality in this clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] In spite of these, fistula identification can be elusive and difficult thus delaying the prompt diagnosis to early childhood or even to adulthood. 7,8 The rarity of the condition and concurrent problems as respiratory distress and gastroesophageal reflux may also postpone the detection of TEF in preterm newborns. 9 Also radiological investigations can be difficult to achieve and may yield increased risk of respiratory arrest especially in a low birth weight and sick infant.…”
Section: Introductionmentioning
confidence: 99%
“…A high level of suspicion is necessary for the diagnosis. The various endoscopic and radiological techniques are not entirely reliable in identifying a fistula [4]. Diagnosis is mostly done by esophagography-esophagoscopy.…”
Section: Discussionmentioning
confidence: 99%